Enalapril Induces Regression of Cardiac Hypertrophy and Normalization of pHi Regulatory Mechanisms - Ennis, Irene Lucía (1998)
Intracellular pH is under strict control in myocardium; H⁺ are extruded from the cells by sodium-dependent mechanisms, mainly Na⁺ /H⁺ exchanger and Na⁺ /HCO₃⁻ symport, whereas Na⁺ -independent Cl⁻ /HCO₃⁻ exchanger extrudes bases on intracellular alkalinization. Hypertrophic myocardium from spontaneously hypertensive rats (SHR) exhibits increased Na⁺ /H⁺ exchange activity that is accompanied by enhanced extrusion of bases through Na⁺ -independent Cl⁻ /HCO₃⁻ exchange. The present experiments were designed to investigate the effect of enalapril-induced regression of cardiac hypertrophy on the activity of these exchangers. Male SHR and normotensive Wistar-Kyoto rats (WKY) received enalapril maleate (20 mg/kg per day) in the drinking water for 5 weeks. Gender- and age-matched SHR and WKY were used as untreated controls. Enalapril treatment significantly reduced systolic blood pressure in SHR and completely regressed cardiac hypertrophy. Na⁺ /H⁺ activity was estimated in terms of both steady pHi value in HEPES buffer and the rate of pHi recovery from CO₂ -induced acid load. Na⁺ -independent Cl⁻ /HCO₃⁻ activity was assessed by measuring the rate of pHi recovery from intracellular alkalinization produced by trimethylamine exposure. Regression of cardiac hypertrophy was accompanied by normalization of Na⁺ /H⁺ and Na⁺ -independent Cl⁻ /HCO₃⁻ exchange activities. Inhibition of protein kinase C (PKC) activity with chelerythrine (10 mmol/L) or calphostin C (50 nmol/L) returned both exchange activities to normal values. These results show that angiotensin-converting enzyme inhibition normalizes the enhanced activity of both exchangers while regressing cardiac hypertrophy. Because normalization of exchange activities could be also achieved by PKC inhibition, the data would suggest that PKC-dependent mechanisms play a significant role in the increased ion exchange activities of hypertrophic myocardium and in their normalization by angiotensin-converting enzyme inhibition.